„CD-ACTION” – 25 lat na rynku prasy o grach wideo - Ciszek, Przemysław (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
This article presents the quarter-century history of the video game magazine named CD-Action, which is currently the oldest Polish magazine dealing with its subject and one of the oldest in Europe. Established in 1996, the title has changed publishers several times, and its content has also changed over that time, as the video game market and the expectations of readers are constantly evolving. Currently, its content includes news and reviews of games and also journalism on video games and modern technologies. A significant plus for readers the magazine during most of its existence was the inclusion of CD/DVD discs with full versions of the games discussed in each issue.